PERBANDINGAN KECENDERUNGAN PENELITIAN PENDIDIKAN MATEMATIKA DI INDONESIA DAN AUSTRALIA - Zagoto, Lidwina Shinta; Giawa, Yulina; Ritonga, Roy Ricardo; Sihombing, Dame Ifa; Manik, Efron (Universitas Quality, 2023)
This article discusses the comparison of trends in mathematics education research in Indonesia and Australia. There are significant differences in research approaches, research focuses, and issues addressed in both countries. Mathematics education research in Indonesia often focuses on improving teacher capabilities, the use of technology in mathematics learning, and the influence of teaching approaches on mathematics learning outcomes. In Australia, research also involves studying mathematics curriculum, effective teaching strategies, inclusion issues in mathematics learning, and the use of technology in teaching. The research approaches also differ, with Indonesia tending to use quantitative approaches and Australia using both quantitative and qualitative approaches. This article provides valuable insights for the development of mathematics education in both countries. By learning from and sharing experiences with each other, both countries can leverage their strengths to enhance the quality of mathematics education at the national level.